Cornelia de Lange Syndrome as Paradigm of Chromatinopathies - Parenti, Ilaria; Kaiser, Frank J. (Frontiers in Neuroscience, 2021)
Chromatinopathies can be defined as a class of neurodevelopmental disorders caused by mutations affecting proteins responsible for chromatin remodeling and transcriptional regulation. The resulting dysregulation of gene expression favors the onset of a series of clinical features such as developmental delay, intellectual disability, facial dysmorphism, and behavioral disturbances. Cornelia de Lange syndrome (CdLS) is a prime example of a chromatinopathy. It is caused by mutations affecting subunits or regulators of the cohesin complex, a multisubunit protein complex involved in various molecular mechanisms such as sister chromatid cohesion, transcriptional regulation and formation of topologically associated domains. However, disease-causing variants in non-cohesin genes with overlapping functions have also been described in association with CdLS. Notably, the majority of these genes had been previously found responsible for distinct neurodevelopmental disorders that also fall within the category of chromatinopathies and are frequently considered as differential diagnosis for CdLS. In this review, we provide a systematic overview of the current literature to summarize all mutations in non-cohesin genes identified in association with CdLS phenotypes and discuss about the interconnection of proteins belonging to the chromatinopathies network.